Determination and Comparison of Ohmic Values of Electrical Resistors from Four Different Methods - Mpanda, Kundakama (European Journal of Applied Sciences, 2022)
During this research, laboratory experiments were carried out on the live ohmic resistors to determine and compare them with other resistors of different ohmic values in order to facilitate the understanding of the first and second-year students in the Computer Engineering and Hydraulic Engineering and Water Sanitation Department through laboratory experiments performed in the physics laboratory of the Polytechnic Institute of the University Kimpa Vita in the Province of Uige in Angola. We used four methods: determination with colour code, determination with a digital multimeter, determination with an analog multimeter, and determination with the first ohm’s law. The results and observations obtained are presented as follows: It can be verified that the determination with colour code appears easier for the students because it does not require the use of any measuring instrument. It was verified that most parts of the resistors that were determined had experimental values close to the nominal values indicated by the manufacturers. De acordo com os dados obtidos durante o experimento, foi possível concluir que as resistências internas interferem nas medições dos instrumentos utilizados, dependendo da relação entre a resistência do circuito medido no caso do dispositivo analógico e da lei de OHM, do instrumento utilizado e seu posicionamento na medição. Verificou-se também que os valores calculados com código de cor são indicados pelos fabricantes (valores nominais). Também descobrimos que são ligeiramente maiores (0,01%) do que os encontrados com outros métodos utilizados.